ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI OPINI AUDIT GOING CONCERN - Wenny Anggeresia Ginting (Universitas Ahmad Dahlan, 2018)
This research is to examine and analyze the influence of audit opinion, leverage and financial distress of previous year to going concern audit opinion on consumer goods company listed in Indonesia Stock Exchange Period 2010-2014. The research approach is quantitative research method. The type of research used is descriptive research. The population of this study are consumer goods companies listed on the Indonesia Stock Exchange Period 2010-2014 as many as 35 companies. A sample of 22 consumer goods companies listed on the Indonesia Stock Exchange in 2010-2014. The result of the research is leverage and Financial distress does not negatively affect going concern audit opinion on consumer goods companies listed in Indonesia Stock Exchange Period 2010-2014. While the previous year audit opinion has a positive effect on going concern audit opinion on consumer goods companies listed in Indonesia Stock Exchange Period 2010-2014. Financial distress, leverage and audit opinion in the previous year had a positive effect on going concern audit opinion on consumer goods companies listed in Indonesia Stock Exchange Period 2010-2014.